2011
DOI: 10.1002/aenm.201100435
|View full text |Cite
|
Sign up to set email alerts
|

Superacidic Electrospun Fiber‐Nafion Hybrid Proton Exchange Membranes

Abstract: A novel type of hybrid membrane has been fabricated by incorporating superacidic sulfated zirconia (S‐ZrO2) fibers into recast Nafion for proton exchange membrane fuel cells (PEMFCs). With the introduction of electrospun superacidic fiber mats, a large amount of protogenic groups aggregated in the interfacial region between S‐ZrO2 fibers and the ionomer matrix, forming continuous pathways for facile proton transport. The resultant hybrid membranes had high proton conductivities, which were controlled by select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…4(b)), the electrospun membrane shows slightly larger ionic clusters (black dots stained by silver nitrate solution) on the interfaces between the SPPESK nanofibers and the SPPESK matrix. It is also evidenced by Yao et al that they observed larger amount of ionic clusters at the interface between hydrophilic sulfated zirconia electrospun fibers and Nafion interfiber voids filler through TEM images [22]. It suggests that large specific surface area of the hydrophilic nanofibers and good interfacial compatibility promote the aggregations of the sulfonic acid groups in the SPPESK interfiber voids filler along the surface of the SPPESK nanofibers.…”
Section: Proton Conductivity Of the Sppesk Electrospun Membranesmentioning
confidence: 77%
See 2 more Smart Citations
“…4(b)), the electrospun membrane shows slightly larger ionic clusters (black dots stained by silver nitrate solution) on the interfaces between the SPPESK nanofibers and the SPPESK matrix. It is also evidenced by Yao et al that they observed larger amount of ionic clusters at the interface between hydrophilic sulfated zirconia electrospun fibers and Nafion interfiber voids filler through TEM images [22]. It suggests that large specific surface area of the hydrophilic nanofibers and good interfacial compatibility promote the aggregations of the sulfonic acid groups in the SPPESK interfiber voids filler along the surface of the SPPESK nanofibers.…”
Section: Proton Conductivity Of the Sppesk Electrospun Membranesmentioning
confidence: 77%
“…It is reported that the proton conductivity can be enhanced for more than 10 folds by means of the single electrospun polyelectrolytic nanofiber, as compared with its bulk membrane [17,18]. Therefore, Nafion, non-fluorinated polyelectrolytes and even inorganic proton conductors have been electrospun into nanofiber mats, and then the interfiber voids are filled with antiswelling polymers (either polyelectrolytic or uncharged) to prepare PEMs [19][20][21][22][23][24][25][26]. While these electrospun membranes often show tradeoff between proton conductivity and mechanical stability [19,[22][23][24].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Particularly, a wide array of versatile nanomaterials synthesized via different methodologies can be harnessed to afford flexible control over nanoscale features. For example, the incorporation of nanofibers induced the formation of nanochannels that are more continuous at the interfaces; ii) multiple phases (polymer phase, nanofiller phase, and interfacial nanochannel phase), each designed to serve specific functions; and iii) synergistic effects that can emerge when the interfacial microenvironment is suitably manipulated.…”
Section: Nanostructured Polymer–filler Composite Membranesmentioning
confidence: 99%
“…As one-dimensional nanomaterials, CNTs have a great advantage over the application of nanocomposite IEMs, compared to zero-dimensional nanomaterials (titanium oxide, iron oxide, silica oxide nanoparticles, etc.). It has been reported that ion pathways exist at the interface of nanomaterials and polymer; hence, long-distance ionic pathways could be formed when elongated nanomaterials (nanotubes or nanofibers) are used [44]. Long-distance ionic pathways largely improve membrane inner structure and facilitate ion transport.…”
Section: Introductionmentioning
confidence: 99%